The Contribution of Islamic Attributes in Influencing the Formation of Destination Image and Destination Loyalty: Domestic Tourists' Perspectives on Halal Tourism - Fajriyati, Ilisa; Harnida, Muthia; Ade Mayvita, Prihatini (International Journal of Science, Technology & Management, 2026)
One of Muslim tourists’ consideration when traveling is the ease of fulfilling their religious obligations and choosing the type of tourism that suits their values. They must ensure the availability of Islamic attributes, the attributes that serve the needs of Muslim tourists. This research aims to examine how these Islamic attributes influence the formation of destination image and how it effects Muslim tourists’ loyalty toward the destination. The research conducted through a survey method with an online questionnaire to 150 Indonesian Muslim tourists as the sample for this study. The result of the study revealed that the Islamic attributes significantly and positively influence the formation of destination image, and in turn, the destination image also found significantly impact the tourists’ loyalty, both behavioral and attitudinal. These results can also provide the managerial implications for the tourism related parties regarding what needs to be maintained and improved in order to increase the tourist visitation.